Impact of dietary supplementation of cinnamon oil on the oxidative stress indices, immune response and intestinal morphology in broiler chickens - RAINA DONERIA; MEENU DUBEY; M K GENDLEY; DURGA CHOURASIA; RUPAL PATHAK; R C RAMTEKE; SONALI PRUSTY; M S PARMAR (Indian Journal of Animal Sciences, 2022)
An experiment was conducted to study the effect of different levels of cinnamon essential oil (CEO) on the oxidative stress indices, immune response and intestinal morphology of broiler chickens. Day old broiler chicks (n=180) were randomly allocated to six dietary groups. Control group (T0) was fed basal diet without antibiotic growth promoter (AGP), Group 2 basal diet with AGP (T1) while basal diet containing graded level of CEO (200, 300, 400 and 500 mg/kg) was fed to Groups T2, T3, T4 and T5 respectively. Significantly lower concentration of Malondialdehyde (MDA) was reported in birds fed CEO supplemented diet as compared to control. Significantly increased villi height was observed in histological section of duodenum and jejunum due to increase in concentration of CEO in T3, T4 and T5 as compared to control. No significant change in the histo-morphology of liver was observed due to supplementation of CEO at different levels in the diet of broiler chicken. It is concluded that dietary supplementation of cinnamon essential oil @ 400 mg/kg improved the immune response and intestinal morphology of broiler chickens without any adverse effect.